TRANSITION OF ONLINE SINGLE SUBMISSION (OSS 1.1 TO RISK-BASED APPROACH) TO INCREASE INVESTMENT IN WEST SUMATERA - Upita Anggunsuri; Zahara Zahara (Jurnal Cendekia Hukum, 2023)
The implementation of an online single submission risk-based approach (OSS RBA) is a manifestation of a government program to increase investment in a region. Business risk classification is an instrument of the Central Government and Local Government in controlling business activity. This study aims to find out the readiness of the local government to implement an online single submission risk-based approach. The method of the study is empirical legal research. The result of this study shows that Padang City has issued Mayor Regulation No 43 /2021 on Guidelines and Procedures of an online single submission risk-based approach Supervision as a follow-up to Government Regulation No. 5/2021 on implementation of online single submission risk-based approach; meanwhile, several other regions are in the process of drafting local regulations relate to implementing online single submission risk-based approach in West Sumatera Province. The challenges of local government to implement OSS RBA consists of indefinite license periods in the particular business field (Appendix I Government Regulation No 5/2021), the regional support system has not integrated OSS RBA and the readiness for the transition from manual RDTR to digital RDTR in West Sumatera.